An area-wide model (AWM) for the euro area - Gabriel Fagan; Jérôme Henry; Ricardo Mestre (European Central Bank (ECB), 2001)
This paper presents a quarterly estimated structural macroeconomic model for the euro area, denoted area-wide model (AWM). This model has been developed with four uses in mind: the assessment of economic conditions in the area, macroeconomic forecasting, policy analysis and deepening understanding of the functioning of euro area economy. Five key features of the model are highlighted. First, it treats the euro area as a single economy. Second, it is a medium sized model which, while detailed enough for most purposes, is nonetheless sufficiently small to be manageable in the context of forecasting and simulation exercises. Third, the model is designed to have a long run equilibrium consistent with classical economic theory, while its short run dynamics are demand driven. Fourth, the current version of the AWM is mostly backward-looking, i.e. expectations are reflected via the inclusion of lagged variables. Finally, the AWM uses quarterly data, allowing for a richer treatment of the dynamics, and is mostly estimated on the basis of historical data (rather than calibrated). The paper comprises the following elements. First, a general overview of the structure of the model and of its long-run and short-run properties is provided, with particular emphasis on how the model reaches its steady state. This is followed by a review of the key behavioural equations, showing e.g. the extent to which the standard behavioural equations are capable of fitting the historical euro area data which has been constructed. Finally results from two illustrative simulations are provided, i.e. a fiscal expenditure shock and a change in interest rates. Appended to the main text are the full list of econometric results, the detailed description of the database and the results of stochastic long run simulations. In addition, a companion file comprising all of the quarterly time series underlying the AWM is made available
Keywords: C3; C5; E2; 330; euro area; European Monetary Union; macroeconometric modelling